-1/8(x-3/8)=-1/9(x-3/8)

Simple and best practice solution for -1/8(x-3/8)=-1/9(x-3/8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1/8(x-3/8)=-1/9(x-3/8) equation:


-1/8(x-3/8)=-1/9(x-3/8)

We simplify the equation to the form, which is simple to understand
-1/8(x-3/8)=-1/9(x-3/8)

Reorder the terms in parentheses
+(-0.125x + 0.046875)=-0.11111111111111*(x-0.375)

Remove unnecessary parentheses
-0.125x + 0.046875=-0.11111111111111+*(+x-0.375+)

Reorder the terms in parentheses
-0.125x + 0.046875=+(-0.11111111111111x + 0.041666666666667)

Remove unnecessary parentheses
-0.125x + 0.046875=-0.11111111111111x + 0.041666666666667

We move all terms containing x to the left and all other terms to the right.
-0.125x + 0.11111111111111x=0.041666666666667-0.046875

We simplify left and right side of the equation.
-0.01388888888889x=-0.0052083333333333

We divide both sides of the equation by -0.01388888888889 to get x.
x=0.37499999999997

See similar equations:

| 3.25x=-39 | | 6(y+9)+y=4(y+4)-2 | | 9x^2+4x-4=3x^2 | | 1-2x+3=12 | | 2v-16=2 | | 8.25y=-115.5 | | 1-5x-6x=-10 | | 36-1/26(4x)=27-1/26(3x) | | 4x-7=2x-4 | | x+iy=4-2i | | y^2+19y+84= | | 7(1-2x)=-6x-33 | | 62=8n-2 | | 2(x+1)=x-9 | | 8x-7w+4x+8y+3y+5w= | | -x-17=-4x+1 | | c+18=50 | | -6=2z+14 | | 4x-1+2x=5x+4x | | 1.16x=5.80 | | -y+7=2y+7 | | 35-3v=2v+5 | | 8x+2(-5-3x)=8-7x | | 0=7w-34 | | 6y-42=5y+20 | | b-14=28 | | 6n^2+18n=0 | | 3n+10=91 | | 3(x+3)=14 | | (12m-10)(10m+10)= | | 10x-9y+13=0 | | 4m+2=30 |

Equations solver categories